Effects of gold panning on communities: a case study of Shurugwi district, year 2000 -2013 - Mangwende, Simbarashe (Midlands State University, 2015)
This research sought to investigate the problems associated with gold panning among non-panning rural, urban communities and also the gold panners of Shurugwi district. Although there are many potential socio-economic benefits of gold panning, there are numerous negative impacts from these small and inefficient panning operations as a result of wasteful extraction and processing techniques. The panning operations were found to be worsening social and environmental impacts of non-panning communities. The negative effects are already being felt in Shurugwi district were HIV spread has been on the increase, also theft and deaths by panners through poor mining and to a greater extent bully fighting. Extensive land degradation has further contributed to siltation of rivers and dams, destruction of vegetation as well as contamination of water bodies. The impact far outweighs the potential socio-economic benefits of gold panning as urban infrastructure has been at risk as well. The role of the government and other relevant stake holders as enforcers of laws, regulations and promoter of mining development need to be defined. Environmental destructive mining practises persist as there is lack of enforcement and control mechanisms for the gold panners. On the other hand there is need for gold panners in the district to take responsibility for the negative impacts from their livelihood.